ETHNOMUSICOLOGY OF TUAK SONG IN HELEBEIK VILLAGE, LOBALAIN DISTRICT, ROTE NDAO DISTRICT - Huka, Relin Yosi; Selan, Dominggus Y.; Ndolu, Welsi Susana; Bana, Albert Josua (Institut Seni Indoensia Surakarta, 2025)
This research raises the theme of art in culture. Art and culture are an important part of traditional community life. People consider art and culture to be part of their lives. The people of Rote Ndao, especially in Helebeik village, Lobalain subdistrict, generally have unique artistic characteristics related to the process of tapping Nira water. This is related to the singing that is done before the tapping process begins. This song is usually referred to as a lament or request to the authority so that the wiretapping can be carried out well and get maximum results. This song is also an expression of gratitude for the blessings that the people of Rote Ndao always enjoy. This research is a form of Ethnomusicology research.